The critical role of BMP signaling in gastric epithelial cell differentiation revealed by organoids - Fan Hong; Xiaodan Wang; Nanshan Zhong; Ze Zhang; Shibo Lin; Mengxian Zhang; Haonan Li; Yuan Liu; Yalong Wang; Lianzheng Zhao; Xiao Yang; Hongwen Zhou; et al. (Cell Regeneration)
Abstract The efficient differentiation of adult gastric stem cells into specific epithelial cell types is crucial for gastric homeostasis. Although it is well appreciated that the niche plays a critical role in gastric epithelium cell differentiation, the relevant molecular factors and the underlying regulatory mechanisms remain poorly understood. In this study, by combining the knowledge of the niche cells obtained from single-cell RNA sequencing and manipulation of signaling pathways, we achieved effective differentiation of various gastric epithelial cell types in mouse and human gastric organoids. These in vitro differentiated cells showed a similar gene expression profile to those in gastric tissues. Specifically, BMP4 signaling stimulates pit cell and parietal cell differentiation. Furthermore, BMP4 and EGF signaling cooperate to enhance pit cell differentiation, whereas inhibition of TGF-β and BMP4 signaling promotes chief cell differentiation. We demonstrated that Zbtb7b is a novel regulator controlling pit cell differentiation. In addition, BMP4, together with the small molecule Isoxazole 9, promotes parietal and enteroendocrine cell differentiation. Our data also revealed the different requirements of parietal and chief cell differentiation between mouse and human. Together, our findings provide a mechanistic insight into gastric epithelial cell differentiation and uncover its similarities and differences between mouse and human, laying a foundation for future investigation and potential clinical use of gastric organoids.